Prioritisation of wildlife pathogens to be targeted in European surveillance programmes: expert-based risk analysis focus on ruminants - Ciliberti, Alexandre; Gavier-Widén, Dolores; Yon, Lisa; Hutchings, Mike R.; Artois, Marc (Elsevier, 2015)
This study attempted to develop a list of priority pathogens. It is part of a European Union (EU) project dedicated to the surveillance of emerging or re-emerging pathogens of wildlife. Partners of the consortium established an initial list of 138 pathogens of concern, which was reduced to a smaller list of 65 pathogens likely to affect ruminants (i.e., the most costly animal group in the EU over the last 15 years). These 65 pathogens underwent a two-step, expert-based risk analysis: 92 experts graded them with respect to their global importance for animal welfare, species conservation, trade/economic impacts and public health. In step 2, the top 15 pathogens from step 1 were assessed by 69 experts considering seven weighted epidemiological criteria (pathogen variability, host specificity, potential for contagion, speed of spread, presence in Europe, difficulty of surveillance in wildlife and persistence in the environment) for which four options were possible. The responses concerned a wide geographic coverage. The resulting top-list pathogens were ranked as follows: 1. Salmonella enterica, 2. Coxiella burnetii, 3. foot-and-mouth disease virus, 4. Mycobacterium bovis, 5. bluetongue virus, and 6. European tick-borne encephalitis virus. The influence of the characteristics of the respondents, the importance of the levels of uncertainty/variability and the implication of the results are discussed. This work highlights the relevance of developing such lists for preparedness.